The inceptions of Islamic educational institutions in Myanmar - U Tun Aung, Maularna Akbar Shah (Myanmar Muslims Club (Singapore), 2016)
Arrival of Muslims in Myanmar was started by 7th AD or 8 AD as different scholars wrote in their respective paper, differently, however in general majority of the scholars agreed that Muslim existence was seen in the corstal cities of Myanmar in the begining of 8th AD such as Arakan (Sittew), Martaban (Muttama), Baseen (Pathein) and Myait (Margue), etc. In the context of the educational Institutions of Muslims in Myanmar was hardly touched by any scholar in the field of litrature and education. Thr first myanmar Muslim Educational Instuitution was properly launched by a muslim scholor, Muhammad Kasim @ U Nu in the period of Botaw Phayar at Amarapura, Upper Burma. Later, in the period of King Mindon, Kabuli Maulavi establishd a Madrasa at the Palace mosque and Golam Ali Shah estabished Madrasa Muhammadia in Upper Myanmar in the beginning of British Rule. After the arrival of Indian Muslims in Myanmar in the begining of 20 th AD several muslim schools and madarsa were seen at differnet region of myanmar most of them are existed at lower myanmar particularly in yangon.